The future without a past : The humanities in a technological society - Russo, John Paul. (Columbia : University of Missouri Press, 2005)
"Argues that technological imperatives like rationalization, universalism, monism, and autonomy have transformed the humanities and altered the relation between humans and nature. Examines technology and its impact on education, historical memory, and technological and literary values in criticism and theory, concluding with an analysis of the fiction of Don DeLillo" - Provided by publisher.
The future of the humanities in a technological society -- The great forgetting : library, media center, and Las Vegas -- The circle of knowledge : science and the humanistic curriculum from Petrarch to Trilling -- Belief and sincerity -- The tranquilized poem : the crisis of the new criticism -- The disappearance of the self : contemporary theories of autobiography -- Don Delillo : ethnicity, religion, and the critique of technology.
Includes bibliogr. references (p. 243-298)and index.
Keywords: Humanities -- Philosophy; Technology and civilization; Science and the humanities; Humanities -- Study and teaching (Higher); Learning and scholarship -- History